Hidden and self-excited attractors in Chua circuit: synchronization and SPICE simulation. Issue 5 (3rd September 2018) - Kiseleva, M. A.; Kudryashova, E. V.; Kuznetsov, N. V.; Kuznetsova, O. A.; Leonov, G. A.; Yuldashev, M. V.; Yuldashev, R. V.
Graphical Abstract: Two symmetric hidden chaotic attractors (blue), trajectories (red) from unstable manifolds of two saddle points are either attracted to locally stable zero equilibrium, or tend to infinity; trajectories (black) from stable manifolds tend to equilibria. Abstract: Nowadays various chaotic secure communication systems based on synchronization of chaotic circuits are widely studied. To achieve synchronization, the control signal proportional to the difference between the circuits signals, adjust the state of one circuit. In this paper the synchronization of two Chua circuits is simulated in Simulation Programs with Integrated Circuit Emphasis. It is shown that the choice of control signal is not straightforward, especially in the case of multistability and hidden attractors.